2012
DOI: 10.1080/0031322x.2012.718164
|View full text |Cite
|
Sign up to set email alerts
|

Running from our shadows: the performative impact of policy diagnoses in Dutch debates on immigrant integration

Abstract: This article examines the performative politics of claiming policy failure in the integration of immigrants in the Netherlands, often articulated as the failure of 'the multiculturalist model'. Four consecutive 'post-'discourses are distinguished, in which we see the construction of increasingly explicit notions of Dutchness. This idea of the Dutch is as much about the style in which it is articulated as it is about the symbolic resources through which Dutchness is imagined. Examining the national imagination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Some studies have identified a paradox between the dominance of Dutch exclusive national discourse, and the growing obligation imposed on migrants to belong to and prove their loyalty to Dutch society (Reekum and Duyvendak 2012;Verkaaik 2010). Buitelaar and Stock (2010) refer to the conflicting demands that Muslim migrants are confronted with (mandating assimilation yet referring to them solely as Muslims) as a "double bind".…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified a paradox between the dominance of Dutch exclusive national discourse, and the growing obligation imposed on migrants to belong to and prove their loyalty to Dutch society (Reekum and Duyvendak 2012;Verkaaik 2010). Buitelaar and Stock (2010) refer to the conflicting demands that Muslim migrants are confronted with (mandating assimilation yet referring to them solely as Muslims) as a "double bind".…”
Section: Discussionmentioning
confidence: 99%
“…[…] A happy‐go‐lucky multiculturalism is spreading because we are not able to explicate what keeps society together. We say too little about our borders, don't cherish a relation to our own past and treat our language nonchalantly (cited in Van Reekum and Duyvendak, : 456).…”
Section: Anti‐nationalism: An Old Image In a New Contextmentioning
confidence: 99%
“…Hence, anti‐nationalist nationalism is generally overlooked by scholars of contemporary Dutch nationalism. Although rare, there are some works on ‘moderate’ enactments of Dutchness with attention to anti‐nationalism, for example, in public debates on citizenship (Van Reekum : 2014; Van Reekum & Duyvendak ) and urban policy practices (Van Reekum and Van de Berg, ; Verkaaik ; ). Although our article is closely related and complementary to these works given the role of anti‐nationalism in the constitution of national self‐images, it also differs in three respects due to its focus: first, it deals with a more specific discourse, namely, a progressive, intellectual one; second, it analyses anti‐nationalism not only as a politicised but also as an informal, banal form of nationalism; and third, its central dynamic is – rather than between Dutch ‘natives’ and ‘migrants’ – between ‘good’ and ‘bad’ nationalists among the Dutch ‘natives’ themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Public discussion over ‘national identity’ gained prominence during the 1980s in the context of debates over the apparent failure of immigrant integration. Failure of integration had been a major issue for some time already, at least since the drafting of the ‘minorities policy’ in 1983 (Essed and Nimako ; Molleman, ; Van Reekum and Duyvendak ).…”
Section: The Failure Of Integrationmentioning
confidence: 99%
“…As has been argued before in relation to the Dutch case (e.g. Duyvendak et al ; Essed and Nimako ; Lucassen & Lucassen ; Prins ; Van Reekum ; Vink ), the narrative of an all‐too‐tolerant nation experiencing a backlash of nationalism is not an adequate description of the Dutch context but rather itself a particular rhetorical enactment of what was, is and ought to be Dutch, often used in public contention over citizenship and belonging (see also Van Reekum and Duyvendak ). This rhetorical figure works both for those who claim that Dutch nationhood has lost a tolerance typical for it as well as those who claim that the nationalist backlash corrects a lapse into tolerant relativism.…”
Section: Introduction: Tolerant No More?mentioning
confidence: 99%